Impacts of Single‐ and a Multiple‐Species Cover Crop on Soybean Relative to the Wheat–Soybean Double Crop System. Issue 1 (1st June 2019) - Raper, Tyson B.; McClure, M. Angela; Butler, Shawn; Yin, Xinhua; Blair, Ryan
Abstract : Core Ideas: Cereal rye and wheat cover crops produced similar levels of biomass as a multi‐species mix. A preemergence herbicide was required to achieve acceptable, consistent levels of weed control. Cover crop treatment did not significantly impact soybean yields. A wheat–soybean double crop system reduced soybean yields in four of five site‐years. The integration of cover crops into soybean ( Glycine max ) production has many potential benefits, but little information has been collected on the impact of multiple‐species cover crops on the subsequent soybean crop relative to the common wheat ( Triticum aestivum) –soybean double crop. Experiments were established at the West Tennessee Research and Education Center in Jackson, TN in the fall of 2014, 2015, and 2016 and the Research and Education Center in Milan, TN in the fall of 2014 and 2015. Winter treatments included a winter–fallow, cover crops including cereal rye ( Secale cereal ), wheat, crimson clover ( Trifolium incarnatum ), and a five‐way mixture [cereal rye, oats ( Avena sativa ), oilseed radish ( Raphanus sativus ), crimson clover, and hairy vetch ( Vicia villosa ), referred to as mix], and wheat for grain. Treatments were split to evaluate weed suppression relative to the preemergence herbicide, S‐ metolachlor + metribuzin. Largest levels of biomass (commonly 4000+ lb/acre) were associated with the wheat for grain, cereal rye, and mix treatments. Weed control was greatest in cereal rye, wheat for cover and mix treatments, but no treatment provided consistent, acceptable weed control without the use of the preemergence herbicide. Soybean yields were not impacted by cover. The delayed planting of soybeans after wheat for grain negatively impacted yields in four of five site‐years by an average of 20 bushels/acre. Results suggest impacts of single‐ or multiple‐species cover crops on soybean yields may be negligible. Market prices, incentives, and long‐term benefits may be more important than short‐term costs/benefits when selecting a production system.